BahasImplementasi Kebijakan Percepatan Pencegahan Stunting Terintegrasi di Kota Matarama Indonesia - Sebtiara Syahrani Krosby; Siti Atika Rahmi; Mintasrihardi Mintasrihardi (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2024)
Stunting is a chronic nutritional problem caused by multifactorial cross-generational, to emphasize the problem of stunting in Mataram City, the Mataram City Government issued a policy through Governor Regulation Number 68 of 2020 concerning Integrated Stunting Prevention and Acceleration Reduction Actions. Jempong Baru Village is the area with the highest number of stunting cases compared to other villages in Mataram City. This study aims to analyze the implementation process of the integrated stunting prevention acceleration policy in Mataram City whether it has run optimally or not. This type of research is qualitative with a descriptive method. Data collection by interview, documentation, and observation methods. The results of this study show that the implementation of the integrated stunting prevention acceleration policy in Jempong Baru sub-district has not run optimally. Based on the results of the analysis using the theory of Van Meter and Van Horn policy implementation in Jempong Baru Village, it shows that there are still indicators that have not been achieved properly. Like human resources at the lowest level, especially cadres, are still lacking in terms of quantity and quality. Financial resources specifically for stunting do not yet exist. The attitude of the implementers, especially on public understanding of the policy is still lacking. Economic, social and political environmental conditions have not been fully able to support the achievement of the success of integrated stunting prevention policies.